Meaningful Learning in Philosophical Perspective: A Review of Ontology, Epistemology, and Axiology - Rahman Syaiful; Nursalim Mochammad; Khamidi Amrozi (Journal of Education Technology and Inovation, 2024)
Meaningful Learning is a learning approach that emphasizes the meaning and relevance of material to students' lives. This study aims to explore Meaningful Learning through a philosophical perspective, namely ontology, epistemology, and axiology. The method used is a data-based literature review from Lens.org, focusing on relevant articles, journals, and policy reports. This study found that ontologically, Meaningful Learning is rooted in an understanding of the nature of meaningful learning as a close relationship between subject matter and student experience. From an epistemological perspective, Meaningful Learning emphasizes how to gain knowledge through active experience, reflection, and dialogue. Meanwhile, axiologically, Meaningful Learning provides added value in the form of developing 21st-century competencies such as critical thinking, creativity, and collaboration. The results of this study provide an important contribution to the development of more contextual and transformative learning theories and practices in education. Recommendations are also given for the application of Meaningful Learning in various educational contexts in Indonesia.